The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1159/000073724
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Prescribing and Risk of Opiate Overdose among Drug Users in and out of Maintenance Treatment

Abstract: Opiate users (n = 135) from southern England, Glasgow and Edinburgh were interviewed about opiate overdose (lifetime). Fifty-six percent had overdosed. The majority (66%) reported mixing opiates with at least one other drug (mainly alcohol and/or benzodiazepines) at their last overdose. Patients identified misjudgements of purity, mixing drugs and misjudgements of tolerance as causes of overdose. The sample was divided into groups: (1) ‘no prescription’, (2) prescribed ‘diazepam only’, (3) prescribed ‘methadon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 41 publications
(42 reference statements)
3
14
0
1
Order By: Relevance
“…Greater numbers of treatment episodes indicates greater movement in and out of treatment during the study period which may arise due to a chaotic lifestyle with increased exposure to the known risk periods, the first two weeks in treatment and first month off treatment. The increased hazard of death among those with co-prescriptions for benzodiazepines is consistent with previous research (Man, Best, Gossop, Stillwell, & Strang, 2004) and toxicological reports of drug related deaths. (Zador, et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Greater numbers of treatment episodes indicates greater movement in and out of treatment during the study period which may arise due to a chaotic lifestyle with increased exposure to the known risk periods, the first two weeks in treatment and first month off treatment. The increased hazard of death among those with co-prescriptions for benzodiazepines is consistent with previous research (Man, Best, Gossop, Stillwell, & Strang, 2004) and toxicological reports of drug related deaths. (Zador, et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…12 The low perception of risk associated with the loss of tolerance and the high frequency with which this situation occurs among participants (in the last 12 months 44.1% had abstained from heroin for more than 30 consecutive days and 7.1% for 16-30 days) suggest that this factor may play an important role in the overdoses produced in the cities studied. That most users have a better knowledge of the risk of using more or purer heroin than usual than they do of the risk of loss of tolerance is consistent with the results of other studies [22][23][24]32 and may lead users to take more precautions in relation with the former factor than the latter. 22 Many young heroin users in the cities studied are also not conscious of the high risk of overdose from using heroin by the intravenous as opposed to other routes of administration (55.6% did not identify this factor), especially injectors who had not been in contact with syringe exchange or distribution programs, those who had been in prison for a long time and those who lived in Barcelona.…”
Section: Discussionsupporting
confidence: 87%
“…It is not surprising, then, that as in other studies, [22][23][24]32 this factor was by far the most frequent reason for overdose recognized by the young heroin users in the cities studied. In fact, 85.1% identified it in the OEQ or PCQ referring to overdose in general.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A number of studies have identified risk factors associated with fatal and nonfatal opiate overdoses, the most common of which is the concurrent use of heroin and other central nervous system depressants, such as alcohol or benzodiazepines (Mann et al, 2004;Warner et al, 2001;Sporer, 1999;Dark and Zador, 1996). Additionally, opiate overdose often results from a voluntary or involuntary lapse in heroin use, such as those associated with drug treatment (Davoli et al, 1993) and incarceration Seaman, 1998).…”
Section: Introductionmentioning
confidence: 99%